THE INFLUENCE OF BRAND IMAGE, PRODUCT QUALITY AND PRICE PERCEPTION ON SAMSUNG SMARTPHONE PURCHASE DECISIONS (Study on Samsung HP Customers in SMS Shop Matahari Simpanglima Semarang) - Amelia Salsabila; Euis Soliha (Jurnal Ekonomi, 2023)
The purpose of this study was to analyze the influence of brand image, product quality and price perceptions on the purchase decision of a Samsung smartphone at the Matahari Simpanglima SMS Store, Semarang. The sample in this study were 120 people who bought Samsung cellphones at Sinar Mas Cellular Matahari Simpanglima Semarang. The sampling technique used was purposive sampling. The analytical tool used is multiple linear regression analysis. The results of the analysis can be concluded that: brand image has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on purchasing decisions. Price perception has a positive and significant effect on purchasing decisions